Bridge design to Eurocodes, UK implementation proceedings of the Bridge Design to Eurocodes - UK Implementation conference held at the Institution of Civil Engineers, London, UK, on 22-23 November 2010 - Denton, Steve, Dr (ICE, 2011)
As of April 2010, Eurocodes replaced British Standards as the principal design standards for bridges in the UK. In support of the transition, the Bridge Design to Eurocodes: UK Implementation conference, brought important background and explanatory information into the public domain.